Legal and Ritological Dynamics of Personalized "Pillars of Shame" in Chinese Social Credit System Construction - Wang, Keren (The China review, 2024)
This article argues that the construction of the Chinese Social Credit System (SCS) largely adheres to the Confucian ritual legal tradition, serving as a tacit "societal constitutional" framework in contemporary China. On the one hand, the SCS aligns with established normative traditions and moral language inherent in Chinese culture. On the other hand, it represents a divergence from post-WWII transnational constitutionalism and rule-of-law norms, contrasting externally with international standards and internally with socialist rule-of-law narratives. This study examines one of the most ambitious social engineering projects in post-economic reform China, which also represents a significant 21st-century governance-by-data experiment. The first part of the article leverages perspectives from Chinese intellectual history, ritual studies, and comparative legal scholarship as analytical tools to examine the deeper discursive structures within the SCS. The second part uses a transdisciplinary approach to analyze recent instances of data-driven, personalized "public shaming" as urban enforcement by local Chinese authorities. These practices, symbolizing "pillars of shame," function not only as disciplinary mechanisms against chronic debt defaulters, known as lǎolài, but also as public rituals performed to restore trustworthiness in an "always-connected" society.